Incidence of pemphigus in Thrissur district, south India - Kidangazhiyathmana AjithKumar (Indian J Dermatol Venereol Leprol | July-August 2008 | Vol 74 | Issue 4, 2008)
Pemphigus is a common autoimmune blistering disorder in India. However, there are no population based surveys from India available to study the prevalence of this disease. Aims: To estimate the incidence of pemphigus in Thrissur district, Kerala, South India. Methods: Questionnaire based survey was conducted among the practicing dermatologists of Trichur district between 1st January 2001 and 1st January 2002 to determine the incidence of pemphigus in the district. Results: Ten cases of pemphigus vulgaris, one case of pemphigus erythematosus, and two cases of pemphigus foliacious were diagnosed during the study period in a population of 2.9 million in Thrissur district. The average age of pemphigus vulgaris patients was 58years in males [42 to 82 years] and 37 in females [25 to 57 years]. The average age of the two male pemphigus foliacious patients was 46 years [52 and 40 years] and the only pemphigus rythematosus patient was a 45 year-old female.Five cases of pemphigus vulgaris were investigated clinically histopathologically and by using direct immunofl uorescence, while two were investigated clinically and histopathologically, two cases clinically, and one case clinically and with Tzanck smear. Two cases ofpemphigus foliacious were diagnosed with the aid of direct immunofl uorescence and the only case of pemphigus rythematosus was diagnosed with the aid of direct immunofl uorescence. Pemphigus vulgaris was common among females. The incidence of pemphigus in Thrissur district is 4.4 per million. Conclusions: This study indicates that the incidence of pemphigus in Thrissur district is high in comparison to the available studies from Germany, France, and the North African country Tunisia.